KARAKTERISTIK PENDERITA DIABETES MELLITUS YANG BERUMUR ≤44 TAHUN YANG DIRAWAT DI RSUD Dr. RM. DJOELHAM KOTA BINJAI TAHUN 2016-2017 - Kristian Adesaputra Zendrato; Sori Muda Sarumpaet; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Diabetes mellitus (DM) is a communicable diseases which has increasing prevalence every year. World Health Organization (2016) reports that there are 422 million people had DM globally. In the other word, 1 in 11 people around the world live with the disease. Based on data from Riskesdas 2013, proportion of people with DM in Indonesia has increased in the age group ≤44 years, from the age group 15-24 years (1,1%), 25-34 years (2,7%), to 35-44 years (6,1%). This research is descriptive with case series design. The objective is to know the characteristics of ≤44 years old patients of DM in RSUD Dr. RM. Djoelham Binjai in 2016-2017. The population of this research is 110 people, the sample is the same as population. The result shows that the proportion of ≤44 years old patients with DM is highest in the late-adulthood age group (80,9%), male (54,5%), Javanese (42,7%), Moslem (55,5%), Senior High School (44,5%), worker (74,5%), main complaints are fatique with nausea and vomiting (64,5%), Type 2 DM (74,5%), with complications (67,3%) especially chronic complications (70,3%), average blood glucose level (BGL) on admission 237,1 mg/dl, hypoglycemic oral medication (49,1%), non self-cost (79,1%), average length of stay 4,2 days, becoming outpatient (59,1%). The statistical test gives no significant differences among age group based on sex (p=0,770), sex based on complication type (p=0,220), average length of stay based on complication type (p=0,829), complication status based on condition when being out of the hospital (p=0,910). There are significant differences among age group based on diabetic type (0,001), age group based on complication status (p=0,001), average length of stay based on complication status (p=0,001), BGL on admission based on medication type (p=0,001), and complication type based on BGL on admission (p=0,034). It’s suggested to RSUD Dr. RM. Djoelham Binjai to intensify on informing patients. The patients should do routine BGL control, life style and diet improvement, routine exercises, attending counseling and regular medication. Keywords: Characteristics, Diabetes mellitus of ≤44 years old patient